THE NUSPLINGEN LITHOGRAPHIC LIMESTONE - A "FOSSIL LAGERSTAETTE" OF LATE KIMMERIDGIAN AGE FROM THE SWABIAN ALB (GERMANY) (Rivista italiana di Paleontologia e Stratigrafia, 2004)
A short overview is given on the actual excavations within a fossiliferous lithographic limestone site near Nusplingen (western Swabian Alb, SW Germany). In contrast to the better known Early Tithonian Solnhofen Lithographic Limestone, it is much richer in fossils and 0.5 my older (Late Kimmeridgian, Beckeri Zone, Ulmense Subzone). Many of the fossils exhibit an excellent preservation, sometimes even of the organic matter. More than 7.000 specimens have been recorded belonging to almost 300 taxa (plants, microfossils, invertebrates, ichnofossils, and vertebrates).